2013
DOI: 10.1093/bja/aes587
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing preoperative haemoglobin with intravenous iron

Abstract: We know that metaraminol is a sympathomimetic amine which acts on the a1-adrenergic receptor with some stimulation of the b-adrenergic receptors. The combination of increased systemic vascular resistance and increased contractility results in an elevation in arterial pressure. However, the effect of metaraminol (or other sympathomimetics) in patients with Takotsubo cardiomyopathy may be less predictable due to the dysfunctional myocardial response to catecholamine stimulation. Indeed, there is evidence to sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…29 The effectiveness of iron sucrose in increasing Hb also depends on the accuracy of the iron deficiency anemia diagnosis. 30 Hb is unlikely to increase in patients with good iron stores and good functional status. In young patients, iron deficit due to metrorrhagia is easily diagnosed 31 and responds well to treatment.…”
Section: Discussionmentioning
confidence: 95%
“…29 The effectiveness of iron sucrose in increasing Hb also depends on the accuracy of the iron deficiency anemia diagnosis. 30 Hb is unlikely to increase in patients with good iron stores and good functional status. In young patients, iron deficit due to metrorrhagia is easily diagnosed 31 and responds well to treatment.…”
Section: Discussionmentioning
confidence: 95%
“…La efectividad del hierro-sacarosa para aumentar la Hb también depende del grado de precisión con el que se diagnostica la anemia por déficit de hierro 30 . Es improbable que ocurra un aumento de Hb en aquellos pacientes con reservas de hierro suficientes y un buen estado funcional.…”
Section: Discussionunclassified
“…Studies have shown that oral ferrous sulphate is useful for correcting iron deficiency in non-anaemic patients [15]. A recent study has suggested that oral ferrous sulphate does not increase preoperative Hb levels in patients planned for elective total hip or knee arthroplasty [16], however intravenous iron replacement was found to be effective in increasing preoperative Hb in these patients according to another recent study [17].…”
Section: Discussionmentioning
confidence: 99%